Managerial Incentives and Management Forecast Precision - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2013)
Managers have great discretion in determining forecast characteristics, but little is known about how managerial incentives affect these characteristics. This paper examines whether managers strategically choose forecast precision for self-serving purposes. Building on the prior finding that the market reaction to vague forecasts is weaker than its reaction to precise forecasts, we find that for management forecasts disclosed before insider sales, more positive (negative) news forecasts are more (less) precise than other management forecasts. The opposite applies to management forecasts disclosed before insider purchases. These results are consistent with managers strategically choosing forecast precision to increase stock prices before insider sales and to decrease stock prices before insider purchases. Additional analyses indicate that the impact of managerial incentives on forecast precision is less pronounced when institutional ownership is high or when disclosure risk is high, and is more pronounced when investors have difficulty in assessing the precision of managers' information.